24-Hour Movement Guidelines: Descriptive Study with Overweight and Obese Low-Income Children - Bergmann, Gabriel Gustavo (2023)
Objective:This study aimed to examine the prevalence of meeting the 24-Hour Movement Guidelines among overweight and obese (OW/OB)children from low-income conditions and compare this prevalence by gender, age, and body mass index (BMI) classification. Methods:Accelerometer-based physical activity (PA), self-report sleep duration (SD), and screen time (ST) were analyzed in 72 OW/OB eight to 12 years old children (21 girls) from low-income conditions. Results:None of the participants met the recommendations for all three behaviors, and only 9.3% met for two behaviors simultaneously. Recommendations for PA, SD, and ST were met for 18.5%, 51.5%, and 4.9% of children, respectively. The prevalence of meeting the recommendation for SD was higher (p=.027) in younger participants (≤10 years old,65.7%) than for the older ones (>10 years old,37.5%). Conclusion:Noneof OW/OB low-income children met the 24-Hour Movement Guidelines. These results appoint for the urgent attention of health and education professionals inorder to includeopportunities for PApractice and knowledge about sleep and sedentary behaviorsin future interventions.